Regulación responsiva y contratación pública - Alejos Guzmán, Oscar (2025)
Regulation, understood in a broad sense, encompasses all forms in which the state intervenes in the lives of individuals (through regulations and administrative acts). However, over the years, the approach to regulation has changed, especially regarding regulatory techniques and ways to ensure compliance. In this context, responsive regulation emerges as a paradigm shift that involves regulating according to the context. This shift can have significant implications for the Peruvian public procurement regime, specifically in its sanctioning regime. Under a responsive regulation logic, a response strategy can be promoted that better harmonizes the interests of the state (as contractor and regulator) and the private sector (as contractors).